PENINGKATAN KETERAMPILAN MENYIMAK CERITA FIKSI ANAK MENGGUNAKAN MEDIA AUDIO PADA SISWA KELAS V SD - Mustika Dewi, Ika Puspa (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract Teachers consider listening skills are easy to learn so it is not so encouraged within teacher makes learning less motivated to look for right media in listening to lessons will be delivered. General objective of this study is to describe use of audio media can improve listening skills of children’s fiction story fifth grade students of SDN 14 South Pontianak. Research method used is descriptive, form of research is Classroom Action Research, the nature of reseach is collaborative. Subjects in this research were students of class V totaling 25 students. This research was conducted as two cycles, result obtained is ability of teachers to design learning using audio media, on first cycle is 3,64 (very good) and second cycle is 3.88 (very good). The ability of teachers to implement learning by using audio media on first cycle 3,31 (good) and second cycle is 3.80 (very good). Calculation result of average value of fiction children's listening skills using audio media, namely 72.05 in first cycle and second cycle is 81.53, with an increase of 9.48. It can be concluded that use of audio media can improve listening skills of children’s fiction story fifth grade students of SDN 14 South Pontianak. Keywords: Listening Skill, Children Fiction Story, Media Audio